Prevalence of oral lesions and systemic pathology in adults of Cordoba city - Caciva, Ricardo Crhistian (2017)
Fil: Caciva, Ricardo Crhistian. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Estomatología A; Argentina.